Biological exacerbation clusters demonstrate asthma and COPD overlap with distinct mediator and microbiome profiles - Ghebre, M; Pang, P; Diver, S; Desai, D; Bafadhel, M; Haldar, K; Kebadze, T; Cohen, S; Newbold, P; Rapley, L; Woods, J; Rugman, P; et al. (Elsevier, 2018)
Background Exacerbations of asthma and chronic obstructive pulmonary disease (COPD) are heterogeneous. Objective We sought to investigate the sputum cellular, mediator, and microbiome profiles of both asthma and COPD exacerbations. Methods Patients with severe asthma or moderate-to-severe COPD were prospectively recruited to a single centre. Sputum mediators were available in 32 asthma and 73 COPD patients assessed at exacerbation. Biologic clusters were determined using factor and cluster analyses on a panel of sputum mediators. Patterns of clinical parameters, sputum mediators, and microbiome communities were assessed across the identified clusters. Results The asthma and COPD patients had different clinical characteristics and inflammatory profiles, but similar microbial ecology. Three exacerbation biologic clusters were identified. Cluster 1 was COPD predominant, with 27 COPD and 7 asthma patients exhibiting elevated blood and sputum neutrophil counts, proinflammatory mediators (IL-1β, IL-6, IL-6R, TNFα, TNF-R1, TNF-R2, and VEGF), and proportion of the bacterial phylum Proteobacteria. Cluster 2 had 10 asthma and 17 COPD patients with elevated blood and sputum eosinophil counts, Type 2 (T2) mediators (IL-5, IL-13, CCL13, CCL17, and CCL26), and proportion of the bacterial phylum Bacteroidetes. Cluster 3 had 15 asthma and 29 COPD subjects with elevated Type 1 (T1) mediators (CXCL10, CXCL11, and IFN-ϒ) and proportions of phyla Actinobacteria and Firmicutes. Conclusions A biologic clustering approach revealed three subgroups of asthma and COPD exacerbations each with different percentages of overlapping asthma and COPD patients. The sputum mediator and microbiome profiles were distinct between clusters. 85